OBE course analysis and learning reflections / Arnida Jahya...[et al.] - Jahya, Arnida; Mohd Sharif, Sariwati; Abu Bakar, Norida; Ismail, Nor Fuzaina; Zulkifli, Faiz; Ahmad Ridzuan, Ahmad Nur Azam; Md Jelas, Imran (2014)
This paper aims to share the findings of outcome-based education (OBE) analysis done on Human Resource Development (HRM549) course from the Faculty of Business Management that was conducted in one of the public universities. Generally, the curriculum documentation of an academic program includes written program educational objectives (PEOs) at the program level together with the course information for all courses in the program. Course information is a document that provides the details of the course outcomes, teaching methodology, assessment, details of students learning time (SLT), program outcomes-course outcomes (POs-COs) matrix, taxonomy and soft skills matrix that serve as an official guideline to a lecturer to conduct the course, deliver the learning activities and assessment of the students. This OBE course analysis was done as a part of an assignment for the Certificate of Education program conducted by Institute of Leadership and Quality Management (ILQAM) in 2014. Findings of the analysis on this HRM549 course showed that there were several items were not mapped to the course learning outcomes. Henceforth, it was recommended that the lecturer should identify the key important elements in the course analysis that will guide them to map the course learning outcomes with program educational objectives. In conclusion, doing OBE course analysis provides an insight of how the curriculum of a course is being designed (or formulated) using OBE approach.